Credit scheme for improvement of manure management on KPSBU dairy farms: Selection criteria, conditions for loan application, and management of the credit scheme - KPSBU Lembang (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Parties KPSBU Lembang and SIDPI project intended to establish a credit scheme for improvement of manure management on dairy farms of members of KPSBU. The following criteria and conditions will apply for selection of dairy farmers of KPSBU to make use of the credit and the management of a credit Scheme for improvement of manure management.